Death and the afterlife in Japanese Buddhism - Stone, Jacqueline I.; Walter, Mariko Namba (Univ. of Hawai'i Press, 2008)
Mukaekō : practice for the deathbed / Sarah Johanna Horton -- With the help of "good friends" : deathbed ritual practices in early medieval Japan / Jacqueline I. Stone -- Beyond death and the afterlife : considering relic veneration in medieval Japan / Brian O. Ruppert -- Collective suicide at the funeral of Jitsunyo : mimesis or solidarity / Mark L. Blum -- At the crossroads of birth and death : the blood pool hell and postmortem fetal extraction / Hank Glassman -- Funerary Zen : Sōtō Zen death management in Tokugawa Japan / Duncan Ryūken Williams -- The structure of Japanese Buddhist funerals / Mariko Namba Walter -- The price of naming the deat : posthumous precept names and critiques of contemporary Japanese Buddhism / Stephen G. Covell -- The orthodox heresy of Buddhist funerals / George J. Tanabe Jr